O Nordeste como saber escolar: as temáticas regionais/regionalistas impressas nos livros didáticos de história. Um estudo comparado 1930/1950 e 1998/2008 - Nobrega, Alessandra Fernandes (2011)
This work focuses on how the Northeast has been depicted in academic and didactic works over time. To that end, a comparative study had been made between two remarkable periods of Brazilian history, the first from 1930 to 1950 and the second from 1998 to 2008. This timeline has been established on the basis that the first temporal mark, Brazil experienced an intense process of reflection on the regional issues, at that time sought to build a reference on the Brazilian citizen, as well as setting benchmarks for the understanding of a national ethos. Later, from the 1990s, the regional issue is taken up in a new perspective, focusing on aspects of their culture and seeking new interpretations of economic processes and about the region. This study sought to understand how debates concerning the regional history are presented in the textbooks, in both periods referenced above. Thus, we selected a textbook produced for each of the decades mentioned: Jonathan Serrano, History of Brazil, edition of 1931; Rocha Pombo, History of Brazil, 1943 edition; Joaquim Silva, Brazil's History, 1959 edition, and by finally, Boulos Jr., History, Society & Citizenship, 2006 edition. The production of these books relate to the contexts experienced by the Brazilian education with its main pedagogical debates. We also seek to point out the changes that the real teaching history has experienced, as well as to investigate the influence that education policies have focused on the production of historical knowledge in school. We understand that textbooks are works of complex composition involving different actors in their production, marketing and distribution, but mainly because they allow a wide diffusion of a worldview, a cultural history. However, the many possibilities of his interpretation give them a cultural and social dimension difficult to measure, able to reveal unique aspects of the history of national education.